Program Dosen Mengabdi sebagai Upaya Pengembangan Potensi Desa Berbasis Pertanian di Desa Cihideung Udik, Kabupaten Bogor - Safira Qisthina Ayuningtyas; Syafitri Hidayati; Adisti Pematasari Putri Hartoyo; Akhmad Arifin Hadi; Andita Sayekti; Ratih Pratiwi; Eko Sulistyono; Chusnul Arif; Mokhamad Syaefudin Andrianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) IPB organizes a Lecturers Community Service Program, as an innovation of lecturers community service by facilitating lecturers to several villages in Bogor and outside of Bogor to directly interact and provide solutions for the community. The purpose of these activities is to enhance the implementation of science and technology from the university for society welfare. One of the villages partners in this program is Cihideung Udik Village with prominent agricultural potential. More than 60% of the land is used for agriculture. Yet, until now the community still face agriculture problems such as decreasing agricultural land area due to changes into residential house. This condition triggers a decrease in the availability of ground water, and cultivation type or pattern change. Previously the community cultivate paddy, but now the community shifts to plant secondary crops especially corn. Not only that, various complex problems in Cihideung Udik require innovative solution available at universities such as IPB University. Lecturer community service at Cihideung Udik was carried out through the socialization of necessary materials viz., future skills motivation, family financial planning, water saving irrigation, water saving cultivation, agrosilvofarmaka, mapping of village potential and marketing. This activity preceived to be useful and any material delivered by the lecturer in general, were needed by the community. Although there was a material that need to be evaluated in order to increase public knowledge. Therefore, the Lecturer Community Service Program have to evaluate and improve their system in responding to community problems and also continuously improve community welfare.